Problematika Pembelajaran Masa Pandemi hingga Masa Pemulihan Learning Problems from Pandemic Period to Recovery Period - Totok Hari Prasetiyo; Magdalena Putri Nugraheni; Mahfud; Susintowati (SOSIOEDUKASI, 2022)
The pandemic brings medical and non-medical problems, including education. The government, as the holder of control over the regulation of the education curriculum in Indonesia makes policies that aim to provide a way out of the learning difficulties during the pandemic. This study is based on a literature review that was conducted in a deskriptif kualitatif manner. Common learning problems during the pandemic are: internet problems, communication devices or devices, cost constraints, incomplete delivery of material, limited communication constraints, adaptation and teacher competence in relation to learning strategies and technology, and inadequate learning environment conditions. The facilities and solutions that are proclaimed in the curriculum are still considered inadequate to accommodate all the problems that occur. This is evidenced by the learning loss or lethargy of students and teachers during the recovery period.